Hydrogen production via methanol steam reforming over Ni-based catalysts: Influences of Lanthanum (La) addition and supports. (9th February 2017) - Lu, Jichang; Li, Xiaofeng; He, Sufang; Han, Caiyun; Wan, Gengping; Lei, Yanqiu; Chen, Ran; Liu, Pan; Chen, Kezhen; Zhang, Lei; Luo, Yongming
Abstract: The effect of the addition of Lanthanum (La), the different loading of nickel oxide and various supports on the catalytic performance of Ni-based catalysts was investigated for methanol steam reforming to produce hydrogen. TEM, N2 adsorption-desorption, XRD, and TPR were used to characterize the catalysts. Separated NiO particles, La–Ni or La–Ni–Al mixed oxides as well as NiAl2 O4 spinel were detected. The results showed that the addition of lanthanum into Ni-based catalyst decreased the steamed temperature and the selectivity of CO. This change was closely associated with separated NiO particles with the smaller size and higher dispersion as well as the different interaction between NiO particles and support upon the modification of lanthanum. It was also found that the moderate loading of nickel facilitates the catalytic performance for methanol steam reforming due to the generation of separated NiO species with moderate particle size. Moreover, the different interaction strength between nickel species and support could give rise to the difference in the catalytic performance of active Ni species, depending on the support. The Al2 O3 supported catalyst exhibits better conversion of CH3 OH, higher hydrogen selectivity and lower CO selectivity than those of SiO2 and MgO supported catalysts. Highlights: La-Ni/Al2 O3 exhibits excellent performance for H2 production from MSR. The addition of La results in the formation of different forms of Ni species. The moderate loading of Ni facilitates the catalytic performance for MSR. Support gives rise to the difference in interaction with active Ni species.